SYLVESTR LEPKYI IN A SOCIAL-CULTURAL AURA OF THE NATION - Качкан, В. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article investigates the multifaceted figure of Sylvestr Lepkyi in the social-cultural aura of the XIXth– the beginning of the XXth century. It observes his role in the spiritual and national life of Ukrainians, analyses the whole range of his fictional and publicistic works.